Pan-genomics of Ochrobactrum species from clinical and environmental origins reveals distinct populations and possible links - Gohil, Kushal; Rajput, Vinay; Dharne, Mahesh (Genomics, 2020)
Ochrobactrum genus is comprised of soil-dwelling Gram-negative bacteria mainly reported for bioremediation of toxic compounds. Since last few years, mainly two species of this genus, O. intermedium and O. anthropi were documented for causing infections mostly in the immunocompromised patients. Despite such ubiquitous presence, study of adaptation in various niches is still lacking. Thus, to gain insights into the niche adaptation strategies, pan-genome analysis was carried out by comparing 67 genome sequences belonging to Ochrobactrum species. Pan-genome analysis revealed it is an open pan-genome indicative of the continuously evolving nature of the genus. The presence/absence of gene clusters also illustrated the unique presence of antibiotic efflux transporter genes and type IV secretion system genes in the clinical strains while the genes of solvent resistance and exporter pumps in the environmental strains. A phylogenomic investigation based on 75 core genes depicted better and robust phylogenetic resolution and topology than the 16S rRNA gene. To support the pan-genome analysis, individual genomes were also investigated for the mobile genetic elements (MGE), antibiotic resistance genes (ARG), metal resistance genes (MRG) and virulence factors (VF). The analysis revealed the presence of MGE, ARG, and MRG in all the strains which play an important role in the species evolution which is in agreement with the pan-genome analysis. The average nucleotide identity (ANI) based on the genetic relatedness between the Ochrobactrum species indicated a distinction between individual species. Interestingly, the ANI tool was able to classify the Ochrobactrum genomes to the species level which were assigned till the genus level on the NCBI database.
Keywords: Antibiotic resistance; Average nucleotide identity; Clinical and environmental strains; Core genes; MinION; Virulence factors